Weight growth velocity in low birth weight neonates receiving parenteral nutrition in the Neonatal Intensive Care Unit, Kandou General Hospital, Manado 2022: a retrospective observational study - Kukihi, Farha Elein; Wiedyaningsih, Chairun; Rina Mutiara (Indonesian Journal of Pharmacology and Therapy, 2024)
Neonates with low birth weight (LBW) have a higher risk of growth failure. To optimize their growth to target of 15-20 g/kg/d, neonates must receive adequate nutrition. Parenteral nutrition implementation is one of the approaches to provide adequate energy and nutrition to LBW neonates who can not tolerate enteral feeding. This study aims to investigate growth velocity in LBW neonates receiving parenteral nutrition in hospital settings and observe if the target growth velocity was achieved, also describes current parenteral nutrition practices in tertiary hospital settings. A retrospective observational study was conducted in the Neonatal Intensive Care Unit (NICU), Kandou General Hospital, Manado. Sample in this study were neonates with birth weight <2500 g and received only parenteral nutrition for minimum 7 d. Daily weight measurement data was collected through medical records and parenteral nutrition regimens was collected through electronic prescriptions in the Pharmacy Department. Growth velocity was assessed using two parameters, gain weight velocity and change in weight for age Z-scores (WAZ). A total of 73 neonates were used as samples. The results demonstrated that only the extremely low birth weight (ELBW) group achieved the growth velocity recommendation during parenteral nutrition, 16.17 g/kg/d. All the neonates had a negative change of weight Z-scores indicated a declining growth rate during parenteral nutrition administration. We also found lipid emulsion initiation time was later and relatively low energy intake in parenteral nutrition compared to the recommendation. Vitamin as micronutrient was not yet added in parenteral nutrition regimens. Therefore, we suggest starting lipid emulsion from the first day of parenteral nutrition and add vitamin to parenteral nutrition regimen to optimize nutrient intake in order to improve growth velocity in LBW neonates during NICU stay.